Quality of Comprehensive Midwifery Care as A Determinants of The Quality of Life of A Postpartum Mother - Susilawati, Dewi; Nilekesuma, Nur Fadjri (JHE (Journal of Health Education), 2020)
Background: One of the strategic efforts to reduce maternal mortality rate (MMR) is through the provision of comprehensive midwifery care. from pregnancy, childbirth to the puerperium. Indicators of success in midwifery care can be seen from the quality of life of postpartum mothers. Preliminary studies in Agam and Pasaman districts show that 50% of post-partum mothers have a poor quality of life. Methods: This analytic descriptive study with a cross-sectional design involved postpartum mother as the subject. The sample of the study was many postpartum mothers who received midwifery services at practicing independent midwives in Pasaman and Agam districts. Samples were taken using the accidental sampling technique within 1 month. A questionnaire for evaluating the quality of life of postpartum women is used as an instrument to measure the quality of life of postpartum mothers. Data were analyzed univariate and bivariate using the chi-square test Results: A total of 75.4% of the research subjects had a good quality of life. There is a relationship between service quality (p= 0.001) and maternal satisfaction (p= 0.001) with the quality of life for postpartum mothers. Conclusion: The better the quality of midwifery services and the level of satisfaction with services, the better the quality of life for postpartum mothers. Therefore, it is recommended that midwives maintain the quality of midwifery care starting from pregnancy, childbirth to childbirth on an ongoing basis (continuity of care).